Gerald D. Schmidt & Larry S. Roberts' foundations of parasitology - Schmidt, Gerals D. (McGraw-Hill, 2005)
A parasitology text for biology and/or zoology students at the undergraduate level. Emphasizes principles with related information on the biology, physiology, morphology, and ecology of the major parasites of humans and domestic animals